2014
DOI: 10.1177/0193945914530047
|View full text |Cite
|
Sign up to set email alerts
|

Moderating Effects of Nurses’ Organizational Support on the Relationship Between Job Satisfaction and Organizational Commitment

Abstract: The aim was to investigate whether job satisfaction enhances organizational commitment among nursing personnel while exploring whether organizational support perception has a moderating effect on the relationship between their job satisfaction and organizational commitment. A cross-sectional survey was sent to 400 nurses; 386 valid questionnaires were collected, with a valid response rate of 96.5%. According to the research findings, nurses' job satisfaction has a positive and significant influence on organiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
52
3
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(71 citation statements)
references
References 60 publications
10
52
3
6
Order By: Relevance
“…On the one hand, nurses' job satisfaction has a positive and significant influence on organisational commitment (Chang, 2014). On the other, organisational commitment has been confirmed to promote job satisfaction (Li, Early, Mahrer, Klaristenfeld, & Gold, 2014).…”
Section: The Impact Of Psychological Empowerment and Organisational Cmentioning
confidence: 95%
“…On the one hand, nurses' job satisfaction has a positive and significant influence on organisational commitment (Chang, 2014). On the other, organisational commitment has been confirmed to promote job satisfaction (Li, Early, Mahrer, Klaristenfeld, & Gold, 2014).…”
Section: The Impact Of Psychological Empowerment and Organisational Cmentioning
confidence: 95%
“…Li, L. (2013) found that perceived organization support played a moderating role in the relationship between person-organization values fit and career success of female high-level person [48]. Chang, C. (2015) discovered nurses' organizational support perception played a regulating effect on the relationship between their job satisfaction and organizational commitment, which indicated the correlation would be stronger for those with higher organizational support perception [49]. Based on the analysis above, we put forward the following hypothesis.…”
Section: The Moderating Role Of Perceived Organization Supportmentioning
confidence: 99%
“…In contrast, abusive leadership practices are associated with low quality of care and high turnover intentions in a sample of nurses working in different units (Lavoie‐Tremblay, Fernet, Lavigne, & Austin, ). Furthermore, nurses with high levels of job satisfaction are more likely to perform extra‐role behaviours at work (Tsai & Wu, ) and display high levels of organizational commitment (Chang, ). Therefore, they may strongly adhere to policies and procedures that have significant effects on patient care.…”
Section: Introductionmentioning
confidence: 99%